PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN SCRAPBOOK TERDAPAT KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA DI KELAS IV SD NEGERI NO. 15 JAWI-JAWI KABUPATEN MAROS - Sri Kurnia Rahman; Syekh Adiwijaya Latief; Anzar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of using scrapbook as a learning medium on thedescriptive writing skills of fourth-grade students at SD Negeri No. 15 Jawi-Jawi, MarosRegency. The main issue identified is the low writing ability of students, as indicated by70% of them not meeting the minimum mastery criteria (KKM). The study employs a quasi-experimental design with a one-group pretest-posttest approach. The subjects consisted of27 students who were purposively selected. The primary instrument used was a descriptivewriting test, which assessed five aspects: object description, content organization,grammar, spelling, and neatness. The pretest results showed an average score of 50, withall students scoring below the mastery standard. After four sessions using the scrapbookmedium, the posttest average significantly increased to 84.26, and all students met themastery criteria. A normality test indicated that the data were normally distributed, and at-test showed a significance value of < 0.05, indicating a significant effect. The findingssuggest that the scrapbook medium is efficacious in improving descriptive writing skills atthe elementary level, as it encourages students to express ideas in a more structured andcreative written form.